Blunt chest trauma in the elderly: an expert practice review. Issue 2 (12th December 2019) - Birse, Fraser; Williams, Helen; Shipway, David; Carlton, Edward
Abstract : Trauma in the elderly (>65 years) is an increasingly common presentation to the ED. A fall from standing height is the most common mechanism after which such patients present, and rib fracture is the most common non-spinal fracture. Thoracic injury in patients aged over 65 is associated with significant morbidity and mortality. There are currently no universally applied guidelines for assessment, investigation and management of such patients. In this expert practice review, we discuss the evidence base and options for clinical management in this vulnerable patient group.